Microbial Community and Metabolic Activity in Thiocyanate Degrading Low Temperature Microbial Fuel Cells - Ni, Gaofeng; Canizales, Sebastian; Broman, Elias; Simone, Domenico; Palwai, Viraja R.; Lundin, Daniel; Lopez-Fernandez, Margarita; Sleutels, Tom; Dopson, Mark (Frontiers in Microbiology, 2018)
Thiocyanate is a toxic compound produced by the mining and metallurgy industries that needs to be remediated prior to its release into the environment. If the industry is situated at high altitudes or near the poles, economic factors require a low temperature treatment process. Microbial fuel cells are a developing technology that have the benefits of both removing such toxic compounds while recovering electrical energy. In this study, simultaneous thiocyanate degradation and electrical current generation was demonstrated and it was suggested that extracellular electron transfer to the anode occurred. Investigation of the microbial community by 16S rRNA metatranscriptome reads supported that the anode attached and planktonic anolyte consortia were dominated by a Thiobacillus-like population. Metatranscriptomic sequencing also suggested thiocyanate degradation primarily occurred via the ‘cyanate’ degradation pathway. The generated sulfide was metabolized via sulfite and ultimately to sulfate mediated by reverse dissimilatory sulfite reductase, APS reductase, and sulfate adenylyltransferase and the released electrons were potentially transferred to the anode via soluble electron shuttles. Finally, the ammonium from thiocyanate degradation was assimilated to glutamate as nitrogen source and carbon dioxide was fixed as carbon source. This study is one of the first to demonstrate a low temperature inorganic sulfur utilizing microbial fuel cell and the first to provide evidence for pathways of thiocyanate degradation coupled to electron transfer.